Statistical techniques to serve quality of software - Shihab, A. Hameed; AlJumaily, A. Asad; Daoud, Jamal Ibrahim (2012)
Within the rapid development of the recent computer-based applications; software quality becomes one of the critical issues to be considered. Software development is complex, costly, widely used, and a core (heart) for critical and risky applications that have great affect on human life. Software testing is an essential issue in software quality. To get an efficient and effective testing we need a proper set of test data. One of the difficult and expensive parts of applying software-testing techniques is the generation of actual or meaningful test data since although there are several techniques and tools to automatically generate test data but mostly they generate meaningless data. This paper proposes a new model for generating meaningful test data. The model is based on using sample of real data and statistical techniques in generation process. The implementation results show that the samples of the generated data are meaningful and reflected the real world or field for testing processes. This leads to enhance the software quality.